Health Risk Assessment of Lead (Pb) and Copper (Cu) Contamination in Sediments of Palu Bay, Indonesia - Matius Paundanan; Sitti Ainun Hikmah; Nely Zulfa (Poltekkes Kemenkes Surabaya, 2026)
Heavy metals are persistent environmental pollutants that tend to accumulate in coastal sediments and may pose long-term ecological and human health risks. This study evaluated the concentrations of lead (Pb) and copper (Cu) in surface sediments of Palu Bay, Central Sulawesi, Indonesia, and assessed potential non-carcinogenic and carcinogenic health risks through dermal exposure. Sediment samples were collected from ten stations representing residential areas, ports, river estuaries, and relatively open zones. Concentrations of Pb and Cu were analyzed using Atomic Absorption Spectrophotometry (AAS) after acid digestion. Sediment contamination was evaluated using the contamination factor (CF) and geoaccumulation index (Igeo), while human health risk assessment (HRA) followed U.S. EPA guidelines. Mean concentrations of Pb and Cu were 6.61 ± 3.64 mg/kg and 20.70 ± 8.83 mg/kg, respectively, and were below international sediment quality guidelines (CCME and ANZECC). CF values (<1) and negative Igeo values indicated low contamination levels. The hazard quotient (HQ) and hazard index (HI) for dermal exposure were below the threshold of concern (HI < 1), suggesting no significant non-carcinogenic risk. Carcinogenic risk (CR) for Pb was within the acceptable range (10⁻⁶–10⁻⁴). Overall, surface sediments in Palu Bay show low levels of Pb and Cu contamination and currently pose minimal health risk through dermal contact. The results provide baseline data to support future monitoring and coastal management strategies.